TECHNIQUE OF WORKING IN WATERCOLOR IN COLOR IMAGE (International journal of artificial intelligence, 2025)
This article analyzes the theoretical foundations of working with watercolor technique in fine arts, stages of historical development, color harmony and its role in the pedagogical process. The role of watercolor technique in the formation of students' aesthetic taste, and in increasing interest in art are revealed. The article also presents the main methods of watercolor technique, rules for creating compositions and methodological recommendations for its use in the educational process.